Analysis Of Geometry Thinking Ability Based on Intellegence Quotient Category in Schoology Assisted Collaborrative Problem Learning (Universitas Negeri Semarang, 2022)
The purpose of this study was to find patterns of students' geometric thinking abilities in terms of intelligence quotient (IQ) on collaborative problem-solving learning (CPS) assisted schoology. The research subjects were 31 students of class VII SMP Negeri 3 Temanggung for the academic year 2020/2021. IQ Score collected by the questionnaire method. Observation, documentation, and interview methods were used to find patterns of geometric thinking ability. Results The study showed that the IQ of the subjects in the focus of the study was found to have four categories, namely high average IQ, average IQ, low average IQ, and borderline defect IQ. The pattern of students ' geometric thinking ability varies for each IQ category. It was found that the pattern of geometric thinking ability was found, especially for the average and low IQ. The wedge pattern occurs because of the impact of CPS learning.